Digital storytelling makes reading fun and entertaining - Abdul Mutalib, Ariffin; Aziz, Nurulnadwan; Shaffiei, Zatul Amilah (Foundation of Computer Science, USA, 2011)
This paper reports on an ongoing study, which determines whether digital storytelling is fun and entertaining.Since the digital storytelling has attracted research attention, children's experience with regards to fun and entertaining when interacting with it should be studied, because they are the generation to utilize the technology.Hence, this study is carried out.This paper starts with some discussions on the background.It highlights the history of reading materials and their chronology.Also, some previous studies on fun and entertaining are reviewed.Then the activities involved in this study are described, including the development of digital storytelling that adapts the user -centered design approach. Further, a user test of the digital storytelling is elaborated including the results obtained. Next, the results are discussed in relation with the experience, before the conclusion section follows at the end.It was found that digital storytelling is really entertaining and invoking fun.